2019
DOI: 10.7554/elife.48293
|View full text |Cite
|
Sign up to set email alerts
|

Neural representation of newly instructed rule identities during early implementation trials

Abstract: By following explicit instructions, humans instantaneously get the hang of tasks they have never performed before. We used a specially calibrated multivariate analysis technique to uncover the elusive representational states during the first few implementations of arbitrary rules such as ‘for coffee, press red button’ following their first-time instruction. Distributed activity patterns within the ventrolateral prefrontal cortex (VLPFC) indicated the presence of neural representations specific of individual st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 80 publications
2
39
0
1
Order By: Relevance
“…As such, RT dynamics may not reflect processes within fronto-parietal cortex, as has been suggested (Ruge and Wolfensteller, 2010). However, Ruge et al (2019) recently showed that newly instructed rules are persistently coded in lateral PFC, even though univariate activity falls to baseline levels, suggesting that these activity dynamics possibly index a different process.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…As such, RT dynamics may not reflect processes within fronto-parietal cortex, as has been suggested (Ruge and Wolfensteller, 2010). However, Ruge et al (2019) recently showed that newly instructed rules are persistently coded in lateral PFC, even though univariate activity falls to baseline levels, suggesting that these activity dynamics possibly index a different process.…”
Section: Discussionmentioning
confidence: 94%
“…In particular, we focused on 'multipledemand' regions in the cingulo-opercular network (CON), the fronto-parietal network (FPN) as well as the striatum (STR). These regions have been implicated in task control (Dosenbach et al, 2008) and also overlap with regions implicated in rule learning and implementation (Hartstra et al, 2011;Stocco et al, 2012;Muhle-Karbe et al, 2017;Ruge et al, 2019), including of hierarchical rules ((Badre et al, 2010).…”
Section: Activity In Striatum and The Cingulo-opercular Network But Nomentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have attempted to address this by developing paradigms where individuals randomly volunteer when to task-switch 10,[13][14][15] . However, these paradigms fail to capture the natural inclination to apply structure to behaviour 16,17 and to optimise behavioural strategies through learning [18][19][20][21][22][23] .…”
mentioning
confidence: 99%
“…More broadly, network neuroscience studies of cognitive control demonstrate that when engaging with a task there is a substantial reorganization of the brain's functional connectome 49,60,61 , characterised by the transition from a state of high-activation to a low-activation highconnectivity state [18][19][20][21][22][23]62 , and this transition rate may depend on learning. Critically, the established task-state expresses a stable 44,62 connectivity pattern that is specific enough to the task 22,47,50,[63][64][65] , cognitive load 22 , performance 66 and clinical abnormalities [67][68][69] to be decoded with machine learning.…”
mentioning
confidence: 99%